(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
A slide fastener (i.e., zipper) is widely used as a secondary material in apparel products. However, the texture of the slide fastener is totally different from the main fabric because the reflection properties change according to the structure or the material. Traditionally, the appearance of the slide fastener has been considered unimportant and so is often concealed. However, recently, novel color technologies such as structural color and mimetic metallic processing have been proposed for slide fasteners made from low-cost plastic. The aesthetics and modern appearance of these new slide fasteners have become attractive to end-users. In spite of the growth of slide fasteners with novel colors, no research has investigated or assessed the applicable photometric or colorimetric methodologies. The absence of a quantitative test method decreases the efficiency of the production of slide fasteners. This study proposes a quantitative methodology to assess the aesthetics of slide fasteners produced with either conventional or the novel color technologies, based on a data set of light reflection properties of slide fasteners. First, the structure of subjective attributes obtained from the human visual sense was analyzed by sensory evaluation and factor analysis. Then, the measurement of the light reflection properties of slide fasteners was conducted with an experimental goniophotometric system developed in this study. The parameters that highly correlated with the subjective scores of representative features were explored. As a result, three principal factors, “profoundness ” , “elegance ” and “novelty ” were identified as aesthetic factors for slide fasteners.